Low-head direct chill slab casting of aluminium alloy AA4045: 3-D coupled turbulent flow and heat transfer study. (30th October 2015) - Hasan, M.; Begum, L.
Abstract : In the present study, a low-head direct chill (DC) industrial-scale caster for rolling ingots has been modelled using the advanced computational fluid dynamics approach. Specifically, the 3-D coupled turbulent melt flow and solidification heat transfer in a slab caster has been modelled for the aluminium AA4045 alloy. The turbulence generated in the melt pool is taken into account in the model through the implementation of a popular low-Reynolds (Re) number version of the k-ε eddy viscosity model. The solidification heat transfer for this complex opaque system has been considered through the employment of the well-known 'enthalpy-porosity' scheme. A staggered control-volume (CV)-based finite-difference scheme is used to discretise the governing transport equations and the associated boundary conditions. The discretised algebraic equations are then solved sequentially using the tridiagonal matrix algorithm with implicit under-relaxation factors. The SIMPLE algorithm was employed to resolve the velocity–pressure couplings in the momentum equations. Three important process parameters of this casting problem, namely, the casting speed, the pouring temperature (inlet melt superheat), and the convective heat transfer coefficient (HTC) at the metal–mould interface for the low-head 30-mm mould, are varied in their corresponding practical range of 60–180 mm min1, 16–64°C and 1000–4000 W m 2 °C, respectively. The predicted results are presented in the form of velocity and temperature fields, solid shell thickness at the mould exit, as well as the sump depth and mushy-region thickness at the centre of the ingot. The obtained results are then critically discussed.